Tropical plants as alternative anthelmintics against Cotylophoran cotylophorum of sheep - CHENNURU, SREEDEVI; KROVVIDI, SUDHAKAR; DAVULURI, TULASI; CHITICHOTI, JYOTHI SREE; KANDI, SUNEETHA (The Indian Journal of Animal Sciences, 2021)
Effect of hydroalcoholic extracts of Pistacia vera L. shell, Anacardium occidentale L. shell, Illicium verum Hook.f. fruit, and Artocarpus heterophyllus Lam seed was assessed in vitro against adult, and lactate dehydrogenase (LDH) of Cotylophoran cotylophorum of naturally infected sheep using worm motility assay and LDH activity assay kit, respectively. Extracts exhibited significant dose- and time-dependent anthelmintic responses by causing mortality of worms. Artocarpus heterophyllus seed exhibited maximum activity with 100% mortality of worms at a higher concentration of 4 mg/mL. Probit analysis revealed that the extracts of A. heterophyllus seed induced 50% worm mortality at a lower concentration (LD50=0.05 mg/mL) compared with those of I. verum fruit (LD50=2.22 mg/mL), P. vera shell (LD50=1.83 mg/mL) and A. occidentale seed (LD50=0.82 mg/mL) extracts. Evidently, A. heterophyllus seed extracts inhibited the LDH activity catalyzing the oxidation of lactate in adult C. cotylophorum. Qualitative screening of the extracts showed existence of amino acids, alkaloids, flavonoids, tannins, and saponins, which are accountable for the anthelmintic effects observed.